The political identities of Muslim local councillors in Britain - Purdam, Kingsley (2000)
There are an estimated 160 local councillors in Britain who are Muslim (May 1996). The party breakdown is as follows: 153 Labour, six Liberal, one Conservative. The councillors are concentrated in areas of Muslim population. For example, there were, in May 1996, 12 Muslim councillors on Birmingham City Council and 11 on Bradford City Council. This paper profiles aspects of the identities and political mobilisations of Muslim local councillors in Britain. The paper draws on findings from a broader research project into the nature of Muslim political mobilisations in Britain. In conclusion, the paper locates Muslim councillors within the wider local polity and outlines an important research agenda. - Reproduced
Keywords: Local government - Great Britain; Local government